Economy Profile of Nicaragua - World Bank Group (World Bank, Washington, DC, 2019)
Doing business 2020 is the 17th in a series of annual studies investigating the regulations that enhance business activity and those that constrain it. Doing business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 190 economies - from Afghanistan to Zimbabwe - and over time. Regulations affecting 12 areas of the life of a business are covered: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, resolving insolvency, employing workers, and contracting with the government. The employing workers and contracting with the government indicator sets are not included in this year’s ranking on the ease of doing business. Data in doing business 2020 are current as of May 1, 2019. The indicators are used to analyze economic outcomes and identify what reforms of business regulation have worked, where, and why. This economy profile presents indicators for Nicaragua; for 2020, Nicaragua ranks 142.